Efeito da adição de feldspato e/ou resíduo de caulin em formulações à base de argila ilítica - Castro, Raimundo José de Sousa (2010)
The red pottery industry in Piauí state is well developed and stands out at the national context for the technical quality of its products. The floor and wall tile industry, however, is little developed since the state has only one company that produces red clay-based ceramic tiles. This thesis aims at using the predominantly illitic basic mass of the above mentioned industry, with the addition of feldspar and/or kaolin residue in order to obtain products of higher technical quality. Kaolin residue consists basically of kaolinite, muscovite mica and quartz; the feldspar used was potassic. In this experiment, basic mass (MB) was used for experimental control and fifteen formulations codified as follows: F2, F4, F8, F16, F32, FR2, FR4, FR8, FR16, FR32, R2, R4, R8, R16 and R32. All raw materials were dry-milled, classified, formulated and then humidified to 10% water. Thereafter, test samples were produced by unixial pressing process in a rectangular steel matrix (60.0 x 20.0 x 5.0) mm3 at (25 MPa). They were fired at four temperatures: 1080°C, 1120°C, 1160°C, with a heating rate of 10°C/min during up to 10 min in an electric oven, and the last one in an industrial oven with a peak of 1140°C, aim ing to confirm the results found in laboratory and, finally, technological tests were performed: MEA, RL, AA, PA, TRF and PF. The results revealed that the residue under study can be considered a raw material with large potential in the industry of red clay-based ceramic tiles, since the results found both in laboratory and in the industry have shown that the test samples produced from the formulations with up to 4% feldspar and those produced with up to 8% feldspar and residue permitted a reduction in the water absorption rate and an increase in the mechanical resistance while those samples produced with up to 4% residue had an increase in the mechanical resistance when compared to those produced from the basic mass and that the formulation with 2% feldspar and residue presented the best technological properties, lowering the sintering temperature down to 1120°C